2011
DOI: 10.1080/15459624.2011.570239
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Dust Exposure: Finishing Activities in Drywall Construction

Abstract: Sanding drywall joint compound is a dusty construction activity. We studied potential factors influencing exposure to respirable and total dust for sanders and bystanders in the area of drywall joint compound finishing in 17 test events within a room-scale isolation chamber. We found the air change rate to be negatively correlated with dust C(twa) both in the sander's personal breathing zone and surrounding area. We could not conclude that sanding tool type systematically influences dust C(twa), but the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The proportion of time spent on each activity by a work crew was consistent across the field sites, with workers spending 4-11% of project time sanding joint compounds (Table I), and was within Values based on chamber test and field observations, (15) rather than chamber tests alone. (4) i Developed by Sheehan et al (16) the reported range of Fischbein et al (1) However, productivity (m 2 of drywall sanded per person-hour) varied among crews, and was highest at Sites 1 and 3 with bifurcated work crews (Table I). At Site 3, drywall finishers were brought onsite after drywall installation along the perimeter area was complete.…”
Section: Results From Field Observationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The proportion of time spent on each activity by a work crew was consistent across the field sites, with workers spending 4-11% of project time sanding joint compounds (Table I), and was within Values based on chamber test and field observations, (15) rather than chamber tests alone. (4) i Developed by Sheehan et al (16) the reported range of Fischbein et al (1) However, productivity (m 2 of drywall sanded per person-hour) varied among crews, and was highest at Sites 1 and 3 with bifurcated work crews (Table I). At Site 3, drywall finishers were brought onsite after drywall installation along the perimeter area was complete.…”
Section: Results From Field Observationsmentioning
confidence: 95%
“…Current joint compounds are formulated with talc, silica, calcite, gypsum, and/or mica . Until the mid–1970s, however, some joint compounds contained chrysotile asbestos as a filler in the range of 5–15% by weight .…”
Section: Introductionmentioning
confidence: 99%
“…An experienced tradesman sanded the wall continuously for eight minutes using a pole sander with 120grit sanding screen. During sanding, respirable dust mass concentrations were collected in the personal breathing zone (on the lapel) of the worker and at randomly selected fixed locations approximately 0.8-3 m from the center of the wall (Simmons et al (23) , Fig. 1).…”
Section: Comparability Of Particle Size Distributionsmentioning
confidence: 99%
“…Room ‐ scale chamber Three testing events were conducted in a 6.1‐m × 6.1‐m × 2.7‐m‐high room‐scale chamber. ( 23 ) A 1.2‐m‐wide × 2.4‐m‐high × 0.12‐m‐thick wall was framed, covered with drywall, and positioned in the center of the chamber. In each test, the drywall was evenly coated with JCN.…”
mentioning
confidence: 99%
“…However, in 2010, the International Agency for Research on Cancer (IARC) released a monograph indicating that titanium dioxide is possibly carcinogenic to humans based on sufficient evidence in experimental animals and inadequate evidence from epidemiological studies (World Health Organization, 2010). In addition to the three particles of concern for this study, additional studies have documented negative health outcomes that are associated with exposure to other occupational abrasion-related particles of concern (Siemiatycki et al, 1989; Simcox et al, 1999; Akbar-Khanzadeh and Brillhart, 2002; Woskie et al, 2004; Young-Corbett and Nussbaum, 2009; Simmons et al, 2011). …”
Section: Introductionmentioning
confidence: 99%